Self-representation of Chinese Migrants Using Digital Storytelling for Social inclusion - Zhang, He (Curtin University, 2017)
Built upon previous digital literacy research, this study reveals opportunities for having a voice that the participatory practice of digital storytelling provides to Chinese international and internal migrants in Australia and China. It identifies potentialities and constraints for digital storytelling in forming and amplifying migrants’ individual voices. It argues that digital storytelling provides migrants with quality access to new media technologies and is useful as a research method for media production in the digital age.